PKB GURU PAUD KARYA INOVASI : PENGGUNAAN GAME INTERAKTIF BERBASIS POWERPOINT DALAM MENINGKATKAN MOTIVASI BELAJAR LITERASI DAN NUMERASI ANAK USIA 5-6 TAHUN DI TK AL-KAFFAH BATAM - Setiyo Otoyo; Ganti Ritauli Sianturi; Taqwa, Rahmi; Prastyo Dwi Indah Lestari; Widiyawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to determine the evaluation and reflection of the use of PowerPoint-based interactive games in increasing motivation to learn literacy and numeracy in early childhood. Through observation methods carried out on children, documentation, and literature studies, various related literature and research were analyzed to gain a comprehensive understanding of the implementation of this approach. The research results show that PowerPoint-based interactive games are able to create an interesting, participatory and child-centered learning atmosphere. Children aged 5-6 years can more easily understand literacy concepts, such as recognizing letters and words, as well as numeracy, such as simple addition, through visual and interactive elements in games. In addition to improving cognitive skills, this approach also has a positive impact on the development of social skills, such as cooperation and communication. However, successful implementation depends on teacher competence in designing technology-based educational content and support from parents. Challenges such as limited technological infrastructure and lack of teacher training need to be addressed through training and providing adequate facilities. In conclusion, PowerPoint-based interactive games have great potential as innovative learning media to support early childhood development, as long as they are supported by collaboration between schools, teachers and parents.